Job Search and Implicit Contracts - Cothren, Richard (Journal of Political Economy, 1983)
A model incorporating costly search and implicit contracts is examined. The contracts differ from those studied in the traditional literature by allowing for both temporary and permanent layoffs. A natural rate of unemployment is determined, and comparative statics analysis shows that changes in the utility value of leisure, in the cost of search, and in the dispersion of prices each have an ambiguous effect on this natural rate.